Effects caused by degeneration of natural frequency for pneumatic isolated table with two degrees-of-freedom - Yui AOKI; Shinji WAKUI (Nihon Kikai Gakkai ronbunshu, 2018)
In this paper, it is confirmed that natural frequency of isolated table is operated and that degeneration, which means that some natural frequencies have the same value, has a bad influence. Pneumatic anti vibration apparatuses (AVAs) support that loaded devices, i.e., XY stages, operate accurately. However, many strict design conditions are imposed on AVAs with six degrees-of-freedom (DOF) which are used on manufacturing floor. There is a risk that the natural frequency of each motion mode approaches, in other words, that isolated table falls into degeneration. This disturbs accurate operations of XY stages. In this paper, AVA with two DOF is used to simplify motion instead of six DOF. First, it is stated that mode control is used to pressure control. Next, position differential feedback (PFB) is proposed. PFB, which is used to the natural frequency control, is applied for each mode. This means that air spring stiffness is considered as each motion mode, and these are deleted or given. It is shown that the natural frequency of each mode can be controlled individually, by calculation, simulation, and experiment. Finally, the degeneration is reproduced to AVA with two DOF by PFB. At this moment, acceleration control which effects to nearby the natural frequency interferes with each other mode. From these results, conclusions are the following: degeneration should be avoided, and mode PFB is effective to control natural frequency of each motion mode. In addition, mode PFB accomplishes not only avoiding degeneration, but also lowering the natural frequency.